Dynamics of Serum Tumor Markers Can Serve as a Prognostic Biomarker for Chinese Advanced Non-small Cell Lung Cancer Patients Treated With Immune Checkpoint Inhibitors - Zhang, Zhibo; Yuan, Fang; Chen, Runzhe; Li, Ye; Ma, Junxun; Yan, Xiang; Wang, Lijie; Zhang, Fan; Tao, Haitao; Guo, Dong; Huang, Zhiyue; Zhang, Sujie; et al. (Frontiers in Immunology, 2020)
Background: Serum tumor markers carcinoembryonic antigen (CEA), cancer antigen 125 (CA125), cytokeratin 19 fragment (CYFRA21-1) and squamous-cell carcinoma-related antigen (SCC-Ag) are routinely used for monitoring the response to chemotherapy or targeted therapy in advanced-stage non-small cell lung cancer (NSCLC), however their role in immunotherapy remains unclear. The aim of this study was to investigate whether dynamics of these serum markers could predict prognosis of patients with late-stage NSCLC treated by programmed cell death-1/programmed cell death ligand-1 (PD-1/PD-L1) inhibitors. Methods: We initiated a longitudinal study on advanced NSCLC patients treated by PD-1/PD-L1 inhibitors. Blood samples of baseline and after 6 weeks' treatment were collected. At least 20% decreases of the biomarkers from baseline were considered as meaningful improvements after 6 weeks of treatment. Optimization-based method was used to balance baseline covariates between different groups. Results: A total of 308 patients with advanced NSCLC were enrolled in the study. After balancing the baseline covariates between different groups, patients with meaningful improvements in less than 2 out of 4 biomarkers was ended up with lower ORR (0.08 vs 0.35, p < 0.001), shorten PFS (5.4 vs 12.5 months, p < 0.001) and OS (11.7 vs 25.6 months, p < 0.001) in the total population. Subgroup analysis of patients with adenocarcinoma (ADC) revealed that patients with meaningful improvements in less than 2 out of 4 biomarkers had significant lower ORR (0.06 vs 0.36, p < 0.001), shorten PFS (4.1 vs 11.9 months, p < 0.001) and OS (11.9 vs 24.2 months, p < 0.001). So as in patients with squamous cell carcinoma (SCC), meaningful improvements in at least 2 out of 4 biomarkers were linked to better ORR (0.42 vs 0.08, p = 0.014), longer PFS (13.1 vs 5.6 months, p = 0.001) and OS (25.6 vs 10.9 months, p = 0.06). Conclusions: The dynamic change of CEA, CA125, CYFRA21-1 and SCC-Ag from baseline could predict efficacy of PD-1/PD-L1 inhibitors in late-stage NSCLC patients. Decrease of associated biomarkers serum levels were associated with favorable clinical outcomes.